2018
DOI: 10.1038/s41598-018-30338-4
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 promotes melanoma metastasis and is involved in the regulation of the EMT associated gene network in melanoma cells

Abstract: We investigated the functional role of CEACAM1 in a spontaneous metastasis xenograft model of human melanoma in scid mice using BRAF wildtype MeWo cells with and without RNAi mediated knockdown of CEACAM1. Tumors from the xenograft model were subjected to whole genome expression analysis and metastasis was quantified histologically. Results and identified markers were verified using tissue samples of over 100 melanoma patients. Knockdown of CEACAM1 prolonged the animals’ survival by significantly reducing subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Chen et al [105] demonstrated that EMT positive human esophageal cancer tissues had higher PD-L1 expression compared to an EMT negative subgroup. Similar studies have shown an association between EMT and immune checkpoint expression in several cancers including thymic carcinoma [106] , melanoma [107] , adeno cystic carcinoma [108] , extrahepatic cholangiocarcinoma [109] and renal cell carcinoma [110] .…”
Section: Role Of Emt In Immune Checkpoint Blockade Therapysupporting
confidence: 62%
“…Chen et al [105] demonstrated that EMT positive human esophageal cancer tissues had higher PD-L1 expression compared to an EMT negative subgroup. Similar studies have shown an association between EMT and immune checkpoint expression in several cancers including thymic carcinoma [106] , melanoma [107] , adeno cystic carcinoma [108] , extrahepatic cholangiocarcinoma [109] and renal cell carcinoma [110] .…”
Section: Role Of Emt In Immune Checkpoint Blockade Therapysupporting
confidence: 62%
“…Interrogating expression of 168 genes using the RT 2 Profiler TM PCR expression array technology, significant changes at the mRNA level affecting twenty-one EMT-related genes were detected [(upregulated): CDH1 , OCLN , IL1RN, PDGFRB, SNAI3 ; (downregulated): BMP1, CDH2, CTNNB1, FN1, FTH1, FZD7, MELTF, MMP2, MMP9, MYC, PTGS2, SNAI2, TFRC, TWIST1, VIM, WNT5A, ZEB1, and ZEB2 (up to tenfold; p < 0.05; Figure 3 A: volcano plot; Figure 3 B: table)]. Strikingly, these genes modulated by GLO1 _KO status encode various factors involved in EMT-like dynamics, as detailed in the discussion [ 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Taken together, these expression changes are consistent with EMT suppression as a result of GLO1 deletion.…”
Section: Resultsmentioning
confidence: 97%
“…Strikingly, differential gene expression array analysis (A375- GLO1 -KO versus A375- GLO1 -WT) revealed pronounced modulation of EMT-related genes ( Figure 3 ). These genes are encoding: ( I ) cellular adhesion factors, signaling molecules, and extracellular matrix components (including BMP1, CTNNB1, CDH1, FN1, FZD7, IL1RN, CDH2, VIM, WNT5A ); ( II ) enzymes involved in extracellular matrix remodeling (including MMP2, MMP9 ) and inflammation ( PTGS2 ); ( III ) transcription factors (including MYC, SNAI2, SNAI3, TWIST1, ZEB1, ZEB2 ); ( IV ) iron-regulatory factors (including FTH1, MELTF, TFRC )—all of which have been shown earlier to control cellular EMT and invasiveness in various tumor types [ 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that ECM components such as collagen, broblasts and their associated signaling molecules contribute to tumor cell proliferation, migration and invasion in various cancers [40,41]. Moreover, IGFBP7 has been reported to regulate epithelial-mesenchylmal transition (EMT) in some solid tumors [12,42,43]. The above results suggest that IGFBP7 and its coexpressed genes may be involved in ECM-related pathways, which would contribute to the utility of IGFBP7 to predict poor prognosis of GC.…”
Section: Discussionmentioning
confidence: 88%